A new species of Theloderma (Amphibia: Anura: Rhacophoridae) from Vietnam - Nguyen, Truong Quang; Pham, Cuong The; Nguyen, Tao Thien; Ngo, Hai Ngoc; Ziegler, Thomas (Zootaxa, 2016)
We describe a new species of Theloderma from northwestern Vietnam based on morphological differences and molecular divergence. Theloderma annae sp. nov. is distinguishable from its congeners on the basis of a combination of the following characters:  Size small, SVL 27.1–28.5 mm in males, 30.3–32.6 mm in females; head longer than wide;  vomerine teeth absent; snout long (SL/SVL 0.16–0.19); spines on upper eyelid absent;  tibiotarsal projection absent; dorsal skin smooth; dermal fringes on forearm and tarsus absent; dorsal surface grayish green; and throat and ventral surface of arms and thighs brown with white spots.